The Effect of GA3 and Salicylic Acid Combination on the Germination and Growth of Kelinci Variety Peanut Sprouts (Arachis Hypogaea L.) Under Aluminum Casting - Primandari, Dea; Lande, Martha Lulus; zulkifli, zulkifli; Yulianty, Yulianty (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This research aims to determine the influence of GA3 and salicylic acid on the germination and growth of Kelinci variety peanuts under aluminum casting. This study was conducted in a 2x3 factorial experiment. Factor A is AL(OH)3 with two concentration levels: 0% b/v and 5% w/v. Factor B is a growing stimulant substance (ZPT) with three levels: GA3 (0.1 % w/v), salicylic acid (0.1% w/v), and GA3 + salicylic acid. The parameters in this study are 1) germinating power, 2) length of sprouts, 3) fresh weight of sprouts, 4) dry weight of sprouts and 5) relative moisture content. The Tukey test determines the main effect, and an F test determines the simple effect. From the research results, the researchers conclude that the mixture of GA3 solution and SA solution is more effective than a single solution of GA3 or SA in overcoming the aluminum's toxic effects on the germination and sprout growth of Kelinci variety peanut.